Religious Tourism Development in Makbaroh Ki Gede Madun Jaya Guwa - Abdurrokhim, Abdurrokhim (Devotion : Journal of Research and Community Service, 2020)
Religious tourism in Makbaroh Ki Gede Madun Jaya tends to be of little interest, even though there are many during kliwon Friday nights. However, it tends to decline on weekdays and needs development. The purpose of this observation or research is to find out the existing problems and find efforts to overcome the existing problems. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews, observation, and documentation. Interviews were conducted with Kuncen Makbaroh, and visitors or pilgrims. The results found from this study are the findings of joint efforts between the village government and the community in developing religious tourism. Based on the results of the above research, the authors conclude: 1) there is togetherness between the government and the community to jointly develop religious tourism as local wisdom in the village of Guwa Kidul, 2) To commemorate Ki Madun Jaya's services in the early spread and develop Islamic teachings in Guwa village South.